Acute Life-Threatening Hemorrhage in Patients with Head and Neck Cancer Presenting with Carotid Blowout Syndrome: Follow-Up Results after Initial Hemostasis with Covered-Stent Placement - Shah, H.; Gemmete, J.J.; Chaudhary, N.; Pandey, A.S.; Ansari, S.A. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: CSP in patients with HNC presenting with CBS can provide immediate hemostasis to prevent exsanguination. We evaluated the safety and efficacy of CSP to control acute life-threatening hemorrhage in patients with HNC presenting with CBS. MATERIALS AND METHODS: We retrospectively reviewed 10 patients (7 men, 3 women; mean age, 59 years) with HNC presenting with acute life-threatening hemorrhage from CBS that was treated with CSP. We studied patient demographics, presentations, procedures, initial and delayed complications, and technical and clinical outcomes on follow-up. RESULTS: All patients achieved immediate hemostasis following CSP. Periprocedural complications consisted of groin hematomas (n = 2), acute limb ischemia requiring thrombectomy, and an asymptomatic temporal lobe hemorrhage. Imaging and clinical follow-up were available for a mean of 17.7 months (range, 1–60 months). Two patients remained asymptomatic with a patent stent and no evidence of rebleeding at 17 and 21 months, respectively. Recurrent hemorrhages requiring retreatment were encountered in 3 patients secondary to stent infections (30%) at mean duration of 8 months. Neurologic morbidity resulted from stent thrombosis and stroke at 8 months in a single patient. Mortality was unrelated to CSP but was a result of palliative hospice care (n = 3) at a mean of 2 months or natural disease progression (n = 1) with documented patency of the stent at 6 months. CONCLUSIONS: Acute life-threatening hemorrhage from CBS related to advanced HNC can be safely and effectively treated with CSP. However, potential delayed ischemic or infectious complications are common in the exposed or infected neck. ACTactivated clotting timeAPanteroposteriorASAacetylsalicylic acidCAcancerCBScarotid blowout syndromeCCAcommon carotid arteryCSPcovered-stent placementCTxchemotherapyDSAdigital subtraction angiographyFFRfree flap reconstructionHNChead and neck cancerICAinternal carotid arteryLleftLCCAleft CCALxlaryngectomyPTFEpolytetrafluoroethylenePxpharyngectomyRrightRCCAright CCARICAright ICARNDradial neck dissectionSCCsquamous cell cancerSNDselect neck dissectionXRTradiation therapy.